Brazilian canvas circuses: a field in constant motion and symbolic transformation - Natt, Elisângela Domingues Michelatto; Aguiar, Ana Rosa Camillo; Carrieri, Alexandre de Pádua (Revista de Administração da UFSM, 2019)
This paper analyzes the circus universe, that is, the circuses and the individuals involved in the daily activities to create, maintain, and develop the circus organization, and is based on Pierre Bourdieu’s field theory. Empirically, we sought to build a qualitative and diversified corpus based on 28 circuses and 116 interviews, as well as recorded conversations, newspaper articles, and by accompanying circuses and watching performances. Particularly, the semi-structured interviews based on the “snowball” technique have the people who work, live, and roam with and in the circus as a common element. Seeking to resist stereotypes and give voice to those who create organizations, we conducted this study so that the various voices of the agents in the field are heard, which, in turn, clarifies how the circus subjects and organizations (the actual circuses) are built and intertwined. No clear domination of an agent over the other has been identified in the field. Except for the legal difficulties pointed out by smaller circuses, power relations are much more visible when it comes to staying in the field. The further the agents are from accessing the symbolic and power resources, the more they are subjected to disappearance or precarious continuity.